2014
DOI: 10.1002/pbc.24969
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary outcomes in patients with Hodgkin lymphoma treated with involved field radiation

Abstract: In survivors of pediatric HL, involved field irradiation was accompanied by a low prevalence of pulmonary symptoms but substantial subclinical dysfunction. Older age at irradiation was associated with worse pulmonary outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Notably, no subjects in our cohort received TBI and only one subject was treated with whole lung irradiation, both of which have been associated with late adverse pulmonary outcomes. 16, 27, 30 While 93% of adolescent subjects in our cohort reported respiratory symptoms in the past month, only half (7/14) reported frequent symptoms (daily or several days of the week). Adolescent questionnaires did not ask about self-reported chronic respiratory symptoms, preventing a direct comparison with parental-reported data.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Notably, no subjects in our cohort received TBI and only one subject was treated with whole lung irradiation, both of which have been associated with late adverse pulmonary outcomes. 16, 27, 30 While 93% of adolescent subjects in our cohort reported respiratory symptoms in the past month, only half (7/14) reported frequent symptoms (daily or several days of the week). Adolescent questionnaires did not ask about self-reported chronic respiratory symptoms, preventing a direct comparison with parental-reported data.…”
Section: Discussionmentioning
confidence: 79%
“…3, 927 Late respiratory complications of anti-neoplastic treatments have been described in children. 823, 25 Additionally, studies have suggested that exposure to some cancer therapies very early in life may increase the risk for long-term sequelae.…”
Section: Introductionmentioning
confidence: 99%
“…Older age [26], the presence of cardiac comorbidities [27] and tumor location in the inferior part of the lung [10,28] were found to increase the risk of lung toxicity significantly. Aging was also associated with worse pulmonary outcome in a pediatric and teenagers cohort [29]. In our previous study [9] on pulmonary complications after HL therapy in a subset of the present patient cohort, the highdose (30 Gy) volume in the left lung appeared to be a better predictor of toxicity than the high dose volume in both lungs.…”
Section: Discussionmentioning
confidence: 87%
“…Survivors of HL are at increased risk of multiple non-cancer morbidities (Aleman et al, 2007;Galper et al, 2011;Schellong et al, 2010;Adams et al, 2004;De Bruin et al, 2009b;Bowers et al, 2005;De et al, 2014;Venkatramini et al, 2014;Oguz et al, 2007;Sklar et al, 2000;Krull et al, 2012;De Bruin et al, 2008;Behringer et al, 2013;van der Kaaij et al, 2012;Daniels et al, 2014;Ruffer et al, 2003;Zebrack et al, 2002;Oerlemans et al, 2011). We have described the number of TYA HL survivors who experienced severe late effects necessitating inpatient hospitalisation and interpreted this as a surrogate marker of morbidity.…”
Section: Discussionmentioning
confidence: 99%